Manhattan Woody’ego Allena. Poetyka Introdukcji - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Woody Allen’s Manhattan. Poetics of the Introduction Marek Hendrykowski’s innovative study on the four-minute opening sequence to Manhattan analyses one of the most beautiful introductions in the history of world cinema. Its subtle simultaneous construction based on European and American traditions and key canonical texts of 20th-century art: Walther Ruttmann’s Berlin: Symphony of the City, John Dos Passos’s Manhattan Transfer and George Gershwin’s Blue Rapsody. A semiotic apparatus has been included, along with deep explanatory commentaries and close-readings that identify step-by-step the details of its content, contradictory fiction-nonfiction relationships, and the roles of visual image, word and music, narrative, personal point of view, and stream of consciousness technique in the film. The suggestive film overture to Manhattan composed by Woody Allen represents continuities as well as disruptions, sustained between avant-garde artistic tradition and film art of the 1970s.